Epigenetic influences on aging: a longitudinal genome-wide methylation study in old Swedish twins. Issue 9 (2nd September 2018) - Wang, Yunzhang; Karlsson, Robert; Lampa, Erik; Zhang, Qian; Hedman, Åsa K.; Almgren, Malin; Almqvist, Catarina; McRae, Allan F.; Marioni, Riccardo E.; Ingelsson, Erik; Visscher, Peter M.; Deary, Ian J.; et al.
ABSTRACT: Age-related changes in DNA methylation were observed in cross-sectional studies, but longitudinal evidence is still limited. Here, we aimed to characterize longitudinal age-related methylation patterns using 1011 blood samples collected from 385 Swedish twins (age at entry: mean 69 and standard deviation 9.7, 73 monozygotic and 96 dizygotic pairs) up to five times (mean 2.6) over 20 years (mean 8.7). We identified 1316 age-associated methylation sites ( P< 1.3×10 −7 ) using a longitudinal epigenome-wide association study design. We measured how estimated cellular compositions changed with age and how much they confounded the age effect. We validated the results in two independent longitudinal cohorts, where 118 CpGs were replicated in Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS, 390 samples) ( P< 3.9×10 −5 ), 594 in Lothian Birth Cohort (LBC, 3018 samples) ( P< 5.1×10 −5 ) and 63 in both. Functional annotation of age-associated CpGs showed enrichment in CCCTC-binding factor (CTCF) and other transcription factor binding sites. We further investigated genetic influences on methylation and found no interaction between age and genetic effects in the 1316 age-associated CpGs. Moreover, in the same CpGs, methylation differences within twin pairs increased with 6.4% over 10 years, where monozygotic twins had smaller intra-pair differences than dizygotic twins. In conclusion, we show that age-related methylation changes persist in a longitudinal perspective, and are fairly stable across cohorts. The changes are under genetic influence, although this effect is independent of age. Moreover, methylation variability increase over time, especially in age-associated CpGs, indicating the increase of environmental contributions on DNA methylation with age.